(untitled) (Saptagandaki Journal, 2025)
The primary objective of the study is to examine the cross-sectional anomalies of stock returns in Nepali capital market. Measures of common stock returns are taken as capital gain yield, dividend yield and total yield. Explanatory variables are stock BETA, total assets growth, firm specific fundamental variables, and specific macroeconomic variables. The research design is descriptive and causal-comparative to investigate the direction, magnitude and nature of relationship between dependent and independent variables following a panel data of 576 (48 listed firms) observations of 2010/11-2021/22. The primary tools of analysis are the portfolio analysis and Ordinary Least Squares (OLS) regression. The findings suggest that the market risk as well as the asset growth have a strong positive impact on cross-section of stock returns in the Nepali capital market. Moreover, firm specific fundamentals variables, and macroeconomic variables are also a major determinant of common stock returns.